137Cs Accumulation by Plants of Floodplain Ecosystems - Oleksandr Lukash; Halina Tkaczenko; Anita Szikura; Natalia Kurhaluk (Proceedings)
The analysis of 137Cs accumulation by plants of forest, marsh, meadow, psamophytic, and ruderal communities in the Dnipro River floodplain (Ukraine) was carried out [...]